Respuesta :

Answer: Option A

Step-by-step explanation:

Given the functions f(x) and g(x):

[tex]f(x) = 3x + 2[/tex]

[tex]g(x)=2x-2[/tex]

[tex](f-g)(x)[/tex] indicates that you need to subtract the function [tex]f(x) = 3x + 2[/tex] and the function [tex]g(x)=2x-2[/tex].

Then:

[tex](f-g)(x)=3x + 2-(2x-2)[/tex]

Now, you need to dstribute the negative sign and then you have to add like terms. Then:

[tex](f-g)(x)=3x + 2-2x+2\\\\(f-g)(x)=x+4[/tex]

You can observe that this answer matches with the option A.

Hello!

The answer is:

A. [tex]x+4[/tex]

Why?

To solve this problem we must remember the following property:

[tex](f-g)(x)=f(x)-g(x)[/tex]

Now, the given functions are:

[tex]f(x)=3x+2\\g(x)=2x-2[/tex]

Then, calculating [tex](f-g)(x)[/tex]

[tex](f-g)(x)=f(x)-g(x)=(3x+2)-(2x-2)\\\\(f-g)(x)=(3x+2)-(2x-2)=3x+2-2x+2\\\\(f-g)(x)=3x+2-2x+2=x+4[/tex]

So, the correct option is:

A. [tex]x+4[/tex]

Have a nice day!